When the steps move the diaspora: The black rio movement and the political-cultural legacy of black soul (19701980 (TEL Tempo, Espaço e Linguagem, 2023)
The following study aims to understand how the dances of the black soul music scene became welcoming spaces for black identities in the 1970s, in Rio de Janeiro. The Black Rio Movement not only captivated the hearts of young people through the popularity of soul music and festivities, but also participated as an important cultural manifestation in the history of the Brazilian black movement. In a creative way, this movement is analyzed as an ally in the process of racial awareness of the subjects. The dances are analyzed as a political-cultural strategy to protect the black community and a response to attempts at oppression and racism by the dictatorship.